Evaluation of Bacilus Thuringiensis Berliner and Baculovirus Heliothis as Microbial Control Agents of Heliothis Armigera (Hubner) and Spodoptera Littoralis (Boisduval) on Tomata. - Lutwama, Julian Julius (Obafemi Awolowo University, 2014)
Field plantings of tomato grown during both the rainy and the dry seasons were subjected to foliar sprays of Bacillus thuringiensis Berliner (B.t.), Baculovirus heliothis (B.h.) and carbaryl, plus Tenac and Gustol adjuvants against larvae of Heliothis armigera (Hubner) and Spodoptera littoralis (Boisduval).